Urologic Injury and Fistula After Hysterectomy for Benign Indications. Issue 2 (August 2019) - Dallas, Kai B.; Rogo-Gupta, Lisa; Elliott, Christopher S.
Abstract : OBJECTIVE: To explore the rates and risk factors for sustaining a genitourinary injury during hysterectomy for benign indications. METHODS: In this population-based cohort study, all women who underwent hysterectomy for benign indications were identified from the Office of Statewide Health Planning and Development databases in California (2005–2011). Genitourinary injuries were further classified as identified at the time of hysterectomy, identified after the date of hysterectomy; or unidentified until a fistula developed. RESULTS: Of the 296, 130 women undergoing hysterectomy for benign indications, there were 2, 817 (1.0%) ureteral injuries, 2, 058 (0.7%) bladder injuries and 834 (0.3%) genitourinary fistulas (80/834 of which developed after an injury repair). Diagnosis was delayed in 18.6% and 5.5% of ureteral and bladder injuries, respectively. Subsequent genitourinary fistula development was lower if the injury was identified immediately (compared with delayed) for both ureteral (0.7% vs 3.4% odds ratio [OR] 0.28; 95% CI 0.14–0.57) and bladder injuries (2.5% vs 6.5% OR 0.37; 95% CI 0.16–0.83). Indwelling ureteral stent placement alone was more successful in decreasing the risk of a second ureteral repair for immediately recognized ureteral injuries (99.0% vs 39.8% for delayed injuries). With multivariate adjustment, prolapse repair (OR 1.44, 95% CI 1.30–1.58), an incontinence procedure (OR 1.40, 95% CI 1.21–1.61), mesh augmented prolapse repair (OR 1.55, 95% CI 1.31–1.83), diagnosis of endometriosis (OR 1.46, 95% CI 1.36–1.56), and surgery at a facility in the bottom quartile of hysterectomy volume (OR 1.37, 95% CI 1.01–1.89) were all associated with an increased likelihood of a genitourinary injury. An exclusively vaginal (OR 0.56, 95% CI 0.53–0.64) or laparoscopic (OR 0.80, 95% CI 0.75–0.86) approach was associated with lower risk of a genitourinary injury as compared with an abdominal approach. CONCLUSION: Genitourinary injury occurs in 1.8% of hysterectomies for benign indications; immediate identification and repair is associated with a reduced risk of subsequent genitourinary fistula formation. Abstract : Genitourinary injury occurs in 1.8% of hysterectomies for benign indications; immediate identification and repair is associated with a reduced risk of subsequent genitourinary fistula formation.